Modern Flow Analysis - Koscielniak, Pawel (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Flow analysis is an automatic, precise and fast way to perform analytical tests. Flow instruments are used for clinical and pharmaceutical analyses, quality control of industrial products, monitoring of environmental pollution and many other fields. The book presents the latest methodological, technical and instrumental achievements in flow analysis. It shows new possibilities for the miniaturization and full mechanization of flow systems, together with examples of their interesting application. The proposed solutions contribute to reducing the amount of used reagents and waste, as well as increasing the safety of working with hazardous reagents, resulting in modern devices operating in accordance with the principles of green chemistry. A number of innovative methods of processing and measuring analytical samples have also been described. The book very well reflects the current state of flow analysis and development directions.